Pengaruh platform pembelajaran daring terhadap prestasi akademik siswa SMP Mitra Eduversal - Nurohman, Nurohman; Hidayatullah, Ahmad Syauqi (Rafandha Press, 2025)
Background: The rapid advancement of digital technology has encouraged the education sector to adopt various online learning platforms to support the teaching and learning process. Purpose: This study aims to determine the effects of using Google Classroom, Zoom Meeting, and Chromebook on students’ academic achievement in online learning at SMP Mitra Kerja Eduversal, as well as to identify which of these platforms is the most effective. Method: A quantitative approach was employed with a population of 140 students. The sample of 103 students was selected using proportional cluster random sampling and the Slovin formula. The research instruments were tested for validity and reliability, followed by assumption testing through normality and homogeneity tests. Data were collected through pretests and posttests, and analyzed using ANOVA. Findings: The results show that the use of Google Classroom significantly improved students' academic achievement, as indicated by the difference between pretest and posttest scores. In contrast, the use of Zoom Meeting did not result in a significant difference between pretest and posttest scores, suggesting limited effectiveness. The use of Chromebooks showed a significant difference between pretest and posttest scores, though its effectiveness was still lower than that of Google Classroom. Therefore, it can be concluded that Google Classroom is the most effective online learning platform among the three in enhancing student achievement at SMP Mitra Kerja Eduversal.